Management and survival of carcinoma of the colon: results of a national survey by the American College of Surgeons. - Evans, J T (1978)
Survey results of long- and short-term outcome audits of colon cancer in participating hospitals with cancer programs conducted during 1976-7 by the American College of Surgeons are presented. In the long-term audit of 38,621 cases reported by 327 hospitals in 46 states, the overall percentage of cases in localized stage (29.3%) is significantly lower than in the recent series from the National Cancer Institute. The observed survival was substantially lower than the survival rates published in recent smaller series; however, survival approaches the end results for the period 1967-1973. In the short-term audit, the analysis of 11,655 cases diagnosed in 1976 and reported by 491 hospitals from fifty states showed that while 41% of patients had symptoms for less than a month, only 29.5% were diagnosed in the localized stage. Surgery was the predominant treatment modality with an overall resectable rate of 83%. No difference was observed in the stage at diagnosis when the short-term audit (1976) was compared with that found in the long-term audit (1971). The results suggest that the early diagnosis of symptomatic patients may not always substantially improve the cure and survival rate. The screening of asymptomatic patients is suggested as the more promising approach to the substantial improvement of presently less than ideal end results.